Wastewater Remediation Technologies Using Macroscopic Graphene-Based Materials: A Perspective - Hirani, Rajan Arjan Kalyan; Asif, Abdul Hannan; Rafique, Nasir; Shi, Lei; Zhang, Shu; Wu, Hong; Sun, Hongqi (Frontiers in Nanotechnology, 2021)
Three-dimensional (3D) graphene-based macrostructures are being developed to combat the issues associated with two-dimensional (2D) graphene materials in practical applications. The 3D macrostructures (3DMs), for example, membranes, fibres, sponges, beads, and mats, can be formed by the self-assembly of 2D graphene-based precursors with exceptional surface area and unique chemistry. With rational design, the 3D macrostructures can then possess outstanding properties and exclusive structures. Thanks to various advantages, these macrostructures are competing in a variety of applications with promising performances unlike the traditional activated carbons, biochars and hydrochars, which have less flexibilities for modifications towards versatile applications. However, despite having such a wide range of applications, 3DMs remain applicable on laboratory scale due to the associated factors like cost and extensive research. This perspective provides an overview of available graphene-based macrostructures and their diverse synthesis protocols. In the synthesis, hydrothermal route, chemical vapour deposition (CVD), wet spinning, 3D printing, vacuum filtration, spray drying and emulsion methods are highlighted. In addition, the physio-chemical properties of these macrostructures are discussed with the relationship among the porosity, surface area and the bulk density. The perspective also highlights the versatile potentials of different 3DMs in wastewater remediation by adsorption, desalination, and catalytic oxidation, etc. Following the concluding remarks, future outlooks on commercial applications of 3DMs are also provided.